2003
DOI: 10.1111/j.1469-7793.2003.00941.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental regulation of hepatic and renal gluconeogenic enzymes by thyroid hormones in fetal sheep during late gestation

Abstract: Tissue glucose-6-phosphatase (G6P) and phosphoenolpyruvate carboxykinase (PEPCK) activities were investigated in sheep fetuses after experimental manipulation of thyroid hormone status. Increments in hepatic and renal G6P and PEPCK activities seen between 127-130 and 140-145 days of gestation (term, 145 ± 2 days) were abolished when the normal prepartum rise in plasma triiodothyronine (T 3 ), but not cortisol, was prevented by fetal thyroidectomy (TX). At 127-130 days, hepatic and renal G6P, and renal PEPCK, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Thus, one explanation of the findings in the present study is that in the subset of hypoxic, hypoglycemic, growth-restricted fetuses in which liver growth is sacrificed, low hepatic glucose uptake results in the increased expression of HSDL1, the enzyme that converts cortisone to cortisol in the hepatocyte. Cortisol has been shown to play a key role in the upregulation of hepatic PCK2 activity and expression in the late-gestation fetus [26,27], so the increase in hepatic HSDL1 mRNA expression and intrahepatic cortisol production may stimulate increased PCK2 mRNA expression.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, one explanation of the findings in the present study is that in the subset of hypoxic, hypoglycemic, growth-restricted fetuses in which liver growth is sacrificed, low hepatic glucose uptake results in the increased expression of HSDL1, the enzyme that converts cortisone to cortisol in the hepatocyte. Cortisol has been shown to play a key role in the upregulation of hepatic PCK2 activity and expression in the late-gestation fetus [26,27], so the increase in hepatic HSDL1 mRNA expression and intrahepatic cortisol production may stimulate increased PCK2 mRNA expression.…”
Section: Discussionmentioning
confidence: 98%
“…PEPCK is the key gluconeogenic enzyme and this nutrionally induced change indicates the fetal need to increase gluconeogenesis in the face of decreased glucose availability. Forhead and colleagues [108] have shown in the chronically catheterized fetal sheep that an increase in PEPCK is one of the many changes the fetus normally makes in late development to prepare to perform gluconeogenesis postnatally. If the neonate has an imbalance in liver glucose metabolism tending towards increased glucose production, that adaptation will be of value if food shortage is experienced postnatally.…”
Section: Principlementioning
confidence: 98%
“…We have suggested that low hepatic glucose uptake results in the stimulation of increased expression of 11βHSD1, the enzyme that converts cortisone to cortisol in the hepatocyte. Cortisol plays a key role in the upregulation of hepatic PEPCK activity and expression in the late gestation fetus [60,61] and so the increase in hepatic 11βHSD1 mRNA expression and intra-hepatic cortisol production may lead to an increase in PEPCK mRNA expression.…”
Section: Iugr Liver Growth and Metabolic Developmentmentioning
confidence: 99%